Syn-eruptive taphoflora from the agua de la zorra formation (upper triassic) cuyana basin, Mendoza, Argentina - Pedernera, Tomas Ezequiel (2019)
In the North of Mendoza Province, at Paramillos de Uspallata locality, Triassic sedimentary rocks outcrop. These Triassic beds include four formations: Paramillos, Agua de la Zorra, Portezuelo Bayo and Los Colorados. The Agua de la Zorra Formation is characterized by deposition in a deltaic and lacustrine system. The aims of this contribution are: (1) to realize a systematic study of new material found in the Agua de la Zorra Formation and (2) to analize the influence of the potential of preservation and the volcanism in the Agua de la Zorra taphoflora in contrast with other Triassic units. Plant remains were systematically collected and compared with taphofloras from other Triassic formations of the Cuyana Basin. The systematic study from the Agua de la Zorra Formation allowed the determination of 21 taxa, nine of which have been cited in a previous contribution and 12 were described for the first time for the Agua de la Zorra formation. There are differences in the taxonomic diversity between the taphofloras recovered from Potrerillos and Paramillos formations and these differences are linking with differences in biostratinomic process in each fluvial system and linked with the evidence of volcanic processes in these areas. The differences in diversity in the taphofloras of the Cacheuta and Agua de la Zorra formations can be more associated to ecological differences than variations in the taphonomic processes in each of the lake systems.